Is venoarterial extracorporeal membrane oxygenation an option for managing septic shock. Issue 1 (15th February 2023) - Helwani, Mohammad A.; Lim, Aaron
Abstract : Purpose of review: To describe sepsis-induced cardiomyopathy. Discuss indications and current evidence of using venoarterial extracorporeal membrane oxygenation (VA-ECMO) in setting of sepsis-induced cardiomyopathy. Recent findings: Recent data suggests a survival benefit with the use of VA-ECMO in patients with septic shock complicated by septic-induced cardiomyopathy with severe left ventricular systolic dysfunction. VA-ECMO was associated with poor outcomes in adults with septic shock without severe systolic dysfunction. The evidence is generated from retrospective and meta-analysis of observational studies. Summary: Sepsis-induced cardiomyopathy is an increasingly recognized entity characterized by reversible ventricular dysfunction in the setting of sepsis. When hypotension persists despite standard management of septic shock (e.g. adequate fluid resuscitation, vasopressors, inotropes) and there is evidence of severe cardiac systolic dysfunction and end-organ hypoperfusion, VA-ECMO should be considered as a bridge therapy to recovery. VA-ECMO should not be used for isolated vasodilatory septic shock without significant myocardial dysfunction.